Distribution Generation Optimal Placement with Various Power Factors and Loading Margins - Gera, Kalidas Babu; rao, Dr. P.V. Ramana (International Journal of Engineering and Technology, 2018)
In the new era of Â power system world depleting conventional resources and increasing rapid power demand leads to focus more on distribution power generation or distribution generation (DG). DG contributes to solve numerous issues like to meet out the peak load demand in distribution system, diminishing power system losses and enhance voltage levels. And one of the major issues of distribution generation is to allocate optimally to hold the most benefits. The work in this paper focuses on the optimal placement of DG by considering pre assumed various power factors along with different loading conditions and the study has been carried out by the technique colliding body optimization. This paper also presents a comparison and influence of variations in DG optimal location with pre assumed load power factors 0.85, 0.87, and 0.89 corresponding to the various loading margins of 0.7, 1.0 and 1.25 of total real power load. The above analysis effectively implemented and tabulated for standard 38 bus system in radial distribution network.